Practice Points: The Challenge of Implementation in Complex, Adaptive Child Welfare Systems: A Realist Synthesis of Signs of Safety - Caffrey, Louise (Practice and Research Together (PART) Candada, 2024)
Complexity science has provided new insights into why implementing policy and practice changes tends to be challenging in complex adaptive systems, including child protection systems. Complexity-informed Realist methods are increasingly used in health sciences research to inform program and policy implementation but have seen little uptake in social work, despite calls to embrace the approach. This paper utilizes a Realist Synthesis to understand and evaluate how interactions between children’s services interventions and the context in which they are introduced can influence implementation and outcomes. Researchers present six emerging program theories on how the interacting effects of reasoning and resources in varying conditions affect the implementation of a popular framework for child protection social work, Signs of Safety. Their findings demonstrate that interactions at multiple systemic levels affect implementation and provide practical guidance to inform service development and delivery and discuss how these findings can inform the basis for a Realist Evaluation of Signs of Safety.
PUBLISHED
Following our invited webinar PART Canada created a 'Webinar Practice Points' publication to disseminate the reserach to practitioners
PART Canada
Keywords: Implementation; Child Welfare; Signs of Safety; Complex Systems; Human Service Organisations